Mother is only one: child malnutrition in Carchi - Rivera Vásquez, Jairo Israel; Olarte Benavides, Stephany Carolina; Rivera Vásquez, Nadya Ximera (SATHIRI, 2020)
Child malnutrition is a problem for the development of Ecuador, where Carchi province has prevalence of chronic malnutrition above the national average, and overweight close to the country's average. The objective of this document was to analyze child malnutrition in Carchi and its evolution during the last two decades. The methodology used was quantitative, through the Surveys of Living Conditions of 1999-2006-2014, using econometric models with probabilistic regression analysis. Among the main results was that child malnutrition presents different determinants of malnutrition and overweight, which highlight the importance of the mother in child’s development.
Keywords: malnutrition; overweight; Ecuador; Carchi; regression analysis